Foreign Policy Making in Colombia the Influence of Non-State Actors - Alviz Hernandez, Maria Alejandra; Druláková, Radka, 1973-; Maslowski, Nicolas, 1972-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
This study is titled Colombia Foreign Policy Making: the influence of non-state actors and its main purpose is to analyze the influence of Non-State actors, violent type and Human Rights NGOs, in the Colombian Foreign policy behavior. It is divided into three respective sections -- a Constructive theoretical framework, the directions of the Colombia Foreign Policy, and the practical part to find the influence of Non-state actors in Colombia Foreign Policy behavior. It strives to answer how Colombian Foreign Policy behavior it's affected by Violent Non-state actors negatively and by Human Rights NGOs.
Vedoucí práce: Radka Druláková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses